2014
DOI: 10.1021/ma402572k
|View full text |Cite
|
Sign up to set email alerts
|

Scattering Function of Wormlike Rings

Abstract: A Monte Carlo (MC) study is made of the scattering function P(k) of the discrete Kratky−Porod (KP) wormlike ring as a function of the magnitude k of the scattering vector, and an approximate formula is also derived for P(k) of the continuous (original) KP ring in the Daniels approximation. It is found from MC results that the peak appearing in the reduced Kratky plot, which is characteristic of the KP ring, lowers continuously from the random-coil-ring limit to the rigid-ring limit with decreasing reduced cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…As a comparison, the single chain structure factor S(q) computed from the MD simulation is also presented in the Kratky form (i.e., S(q)q 2 versus q). In both cases, a peak emerges at the intermediate q range as the fraction of sticker increase-a feature that is indicative of either branching (interchain association) [33][34][35] or loop formation (intrachain association) [36,37]. However, it is important to recognize that the fraction of interchain bonding decreases as the number of stickers per chain increases.…”
Section: Resultsmentioning
confidence: 98%
“…As a comparison, the single chain structure factor S(q) computed from the MD simulation is also presented in the Kratky form (i.e., S(q)q 2 versus q). In both cases, a peak emerges at the intermediate q range as the fraction of sticker increase-a feature that is indicative of either branching (interchain association) [33][34][35] or loop formation (intrachain association) [36,37]. However, it is important to recognize that the fraction of interchain bonding decreases as the number of stickers per chain increases.…”
Section: Resultsmentioning
confidence: 98%
“…The theoretical values agree well with the corresponding MC values in the range of ⟨S 2 ⟩ 1/2 k ≲ 3, where the peak characteristic of the ring appears, for λL ≳ 10. We note that in the ranges of ⟨S 2 ⟩ 1/2 k ≲ 3 and λL ≳ 10, effects of chain thickness on P (k) are negligibly small 40.…”
mentioning
confidence: 76%
“…Although the KP chain model may in principle be extended to other kinds of non-linear polymer chains, the only theoretical studies that emerged thus far investigate the mean-square-radius -4of gyration ⟨S 2 ⟩ of the KP stars by Mansfield and Stockmayer 5 and ⟨S 2 ⟩, the intrinsic viscosity [η], and the translational diffusion coefficient D of the KP ring by Yamakawa's group. [13][14][15] We recently made theoretical and/or Monte Carlo studies of the dilute solution properties of semiflexible star [34][35][36][37][38] and ring 39,40 polymers using the KP wormlike chain model. In this short review, the results of these studies are briefly summarized.…”
Section: Introductionmentioning
confidence: 99%
“…This is an effective method when the wormlike chain parameters may depend on the chain length. While P(q) of the wormlike ring cannot be calculated analytically, Tsubouchi et al [64] developed a Monte Carlo simulation method to calculate the particle scattering function Pc(q) of thin wormlike ring. Furthermore, if the chain thickness is taken into account by the touched-bead model as follows, ( ) (9) we reported that the resultant P(q) successfully reproduced the experimental data for the three amylose derivatives, that is, cATPC, cATBC, and cADMPC [24,44].…”
Section: Analyses In Terms Of the Cyclic Wormlike Chain: Catodcmentioning
confidence: 99%